Potential of essential oils for protection of grains contaminated by aflatoxin produced by Aspergillus flavus - Esper, Renata H.; Gonçalez, Edlayne; Marques, Marcia O. M.; Felicio, Roberto C.; Felicio, Joana D. (Frontiers in Microbiology, 2014)
Aﬂatoxin B1 (AFB1) is a highly toxic and carcinogenic metabolite produced by Aspergillus species on food and agricultural commodities. Inhibitory effects of essential oils of Ageratum conyzoides (mentrasto) and Origanum vulgare (oregano) on the mycelial growth and aﬂatoxin B1 production by Aspergillus ﬂavus have been studied previously in culture medium. The aim of this study was to evaluate aflatoxin B1 production by Aspergillus flavus in real food systems (corn and soybean) treated with Ageratum conyzoides (mentrasto) and Origanum vulgare (oregano) essential oils. Samples with 60 g of the grains were treated with different volumes of essential oils, 200, 100, 50, and 10 μL for oregano and 50, 30, 15, and 10μL for mentrasto. Fungal growth was evaluated by disk diffusion method. Aflatoxin B1 production was evaluated inoculating suspensions of A. ﬂavus containing 1.3×105 spores/ mL in 60 g of grains (corn and soybeans) after adjusting the water activity at 0.94. Aflatoxin was quantified by photodensitometry. Fungal growth and aflatoxin production were inhibited by essential oils, but the mentrasto oil was more effective in soybeans than that of oregano. On the other hand, in corn samples, the oregano essential oil was more effective than that of mentrasto. Chemical compositions of the essential oils were also investigated. The GC/MS oils analysis showed that the main component of mentrasto essential oil is precocene I and of the main component of oregano essential oil is 4-terpineol. The results indicate that both essential oils can become an alternative for the control of aflatoxins in corn and soybeans.